Do the Effects of Police Body-Worn Cameras on Use of Force and Complaints Change Over Time? Results From a Panel Analysis in the Milwaukee Police Department - Peterson, Bryce E. (Criminal justice and behavior, 2021)
Police body-worn cameras (BWCs) can help improve transparency, accountability, and policing behaviors. This study extends prior BWC research by using a panel analysis design with a measure of treatment duration to examine how the effects of BWCs change over time. Using data from the Milwaukee Police Department (N = 1,009), we propose and test two competing hypotheses: The program maturity hypothesis suggests that BWCs will be more effective at reducing use of force and complaints over time, whereas the program fatigue hypothesis expects BWCs to be less effective the longer officers wear BWCs. We find that BWCs reduced complaints overall and that, over time, each additional month with a camera resulted in 6% fewer complaints. There was no overall relationship between BWCs and use of force, but our treatment duration model suggests that there was an immediate decrease in use of force incidents, followed by a gradual increase in subsequent months.